2019
DOI: 10.56093/ijas.v89i11.95339
|View full text |Cite
|
Sign up to set email alerts
|

Crossability studies among Momordica charantia var. charantia and Momordica charantia var. muricata

Abstract: Inter and intra-specific hybridization is a powerful breeding method for crop improvement and it has potential to broaden the genetic base of the cultivated species. M. charantia var. muricata is considered as a wild progenitor of bitter gourd (M. charantia) and it has important novel genes for biotic and abiotic stress tolerance. In the present experiment, conducted during the 2016–17 and 2017–18, intra-specific hybrids were produced among M. charantia var. charantia and M. charantia var. muricata and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Thus, the use of GK Muricata accession as promising germplasm for bitter gourd improvement would be possible. This is in agreement with Rathod et al (2019), who reported a high percentage of fruit set (> 85%) with abundant seeds per fruit and seedling survivability of the cross between M. Charantia var. Charantia and M. Charantia var.…”
Section: Determination Of the Genetic Control Of Traitssupporting
confidence: 93%
“…Thus, the use of GK Muricata accession as promising germplasm for bitter gourd improvement would be possible. This is in agreement with Rathod et al (2019), who reported a high percentage of fruit set (> 85%) with abundant seeds per fruit and seedling survivability of the cross between M. Charantia var. Charantia and M. Charantia var.…”
Section: Determination Of the Genetic Control Of Traitssupporting
confidence: 93%
“…The results are in accordance with the reports of Guler et al (1995) and Rathod et al (2018). Guler et al (1995) reported that most convenient germination medium was 1 per cent agar, 12 per cent sucrose, 300 ppm H 3 BO 3 and 300 ppm Ca(NO 3 ) 2 for in vitro pollen germination of eggplant.…”
Section: Effects Of Different Solid and Liquid Media On Brinjal Polle...supporting
confidence: 91%
“…Guler et al (1995) reported that most convenient germination medium was 1 per cent agar, 12 per cent sucrose, 300 ppm H 3 BO 3 and 300 ppm Ca(NO 3 ) 2 for in vitro pollen germination of eggplant. Rathod et al (2018) compared three in vitro pollen germination media in Momordica spp. and their interspecific hybrids reported that sucrose @ 15 % + Boric acid @ 0.25% + Calcium nitrite @ 300mg solution showed the maximum per cent of pollen germination and pollen tube growth.…”
Section: Effects Of Different Solid and Liquid Media On Brinjal Polle...mentioning
confidence: 99%
“…The mean values recorded for the Harvest duration ranged from 21 days (SWEAKAR-448) to 15.5 days (9005-SIRI). Whereas, the highest harvest duration was recorded in SWEAKAR-448 (20-25) followed by PKM-1 (18)(19)(20)(21)(22), , Arka Vikas (16-17) and the lowest Harvest duration was observed in 9005-SIRI (15-16) respectively. This finding is in agreement with earlier reports that different factors are responsible for plant vegetative growth and fruiting in plants [4,5].…”
Section: Resultsmentioning
confidence: 97%
“…Pollen viability was directly linked to fruit set, whereas formation and fruit set were not in the five tomato varieties that were investigated. Pollen viability was high, which was accompanied through a reduction in the number of fruit sets, fruit size and number of fruits per plant number may be influenced by biotic or abiotic factors [1,[15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%